2012
DOI: 10.4028/www.scientific.net/amm.178-181.2228
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of SFRC Piers under Reversed Cyclic Loading

Abstract: Steel fiber reinforced concrete (SFRC) has many good dynamic performances such as toughness and ductility. However, few studies have focused on SFRC’s application in bearing member of bridge structures. In this paper, pseudo-static cyclic tests of eight pier specimens are carried out to investigate seismic behavior of piers using SFRC. The main variables in the testing are the steel fiber content (volume fraction of 0.0%, 0.5%, 1.0% and 1.5%), the length of SFRC region and the stirrup ratio of piers. Seismic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…FRC and ECC are efficient cement-based composites that can compensate for the drawbacks of quasibrittleness of conventional concrete and has better structural performance than conventional concrete [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Zhang et al [24][25][26] conducted the seismic performance tests of steel fiberreinforced concrete (SFRC) locally reinforced hollow piers at the potential plastic hinges, which showed that the application of SFRC can improve the ductility and bending performance of the piers. Zhang and Dias-da-Costa [27] carried out experiments and finite element analysis to investigate the seismic vulnerability of multispan continuous girder (MSCG) bridges with SFRC piers.…”
Section: Introductionmentioning
confidence: 99%
“…FRC and ECC are efficient cement-based composites that can compensate for the drawbacks of quasibrittleness of conventional concrete and has better structural performance than conventional concrete [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Zhang et al [24][25][26] conducted the seismic performance tests of steel fiberreinforced concrete (SFRC) locally reinforced hollow piers at the potential plastic hinges, which showed that the application of SFRC can improve the ductility and bending performance of the piers. Zhang and Dias-da-Costa [27] carried out experiments and finite element analysis to investigate the seismic vulnerability of multispan continuous girder (MSCG) bridges with SFRC piers.…”
Section: Introductionmentioning
confidence: 99%